Sagot :
✨Answer✨
[tex] x = 0 \: or \: x = - 1 \: or \: x = 3 \: or \: x = \frac{1}{2} [/tex]
✍️EXPLANATION OF THIS ANSWER✍️
[tex]x( x \: + 1)(x - 3)(2x - 1) = 0[/tex]
APPLY ZERO PRODUCT PROPERTY↓
[tex] \times = 0 \: or \: x + 1 = 0 \: or \: x - 3 = 0 \: or \: 2x - 1 = 0[/tex]
⭐SOLVING STEPS⭐
[tex] log(x + 1 = 0) or \: x - 3 = 0 \: or \: 2x - 1 = 0[/tex]
x+1=0↓
Rearrange unknown terms to the left side of the equation:
x=-1
OR
x-3=0
Rearrange unknown terms to the left side of the equation:
x = 3
OR
2x-1=0
Rearrange unknown terms to the left side of the equation:
2x=1
Divide both sides of the equation by the coefficient of variable:
[tex]x = \frac{1}{2} [/tex]
[tex]x = 0 \: or \: x = - 1 \: or \: x = 3 \: or \: x = \frac{1}{2} [/tex]
Combine the results
[tex]x = 0 \: or \: x = - 1 \: or \: x = 3 \: or \: x = \frac{1}{2} [/tex]
Final Answer
[tex]x = 0 \: or \: x = - 1 \: or \: x = 3 \: or \: x = \frac{1}{2} [/tex]